Impact of ionizing radiation on cell-ECM mechanical crosstalk in breast cancer - Mottareale, Rocco; Frascogna, Crescenzo; La Verde, Giuseppe; Arrichiello, Cecilia; Muto, Paolo; Netti, Paolo A.; Fusco, Sabato; Panzetta, Valeria; Pugliese, Mariagabriella (Frontiers in Bioengineering and Biotechnology, 2024)
The stiffness of the extracellular matrix plays a crucial role in cell motility and spreading, influencing cell morphology through cytoskeleton organization and transmembrane proteins' expression. In this context, mechanical characterization of both cells and the extracellular matrix gains prominence for enhanced diagnostics and clinical decision-making. Here, we investigate the combined effect of mechanotransduction and ionizing radiations on altering cells' mechanical properties, analysing mammary cell lines (MCF10A and MDA-MB-231) after X-ray radiotherapy (2 and 10 Gy). We found that ionizing radiations sensitively affect adenocarcinoma cells cultured on substrates mimicking cancerous tissue stiffness (15 kPa), inducing an increased structuration of paxillin-rich focal adhesions and cytoskeleton: this process translates in the augmentation of tension at the actin filaments level, causing cellular stiffness and consequently affecting cytoplasmatic/nuclear morphologies. Deeper exploration of the intricate interplay between mechanical factors and radiation should provide novel strategies to orient clinical outcomes.